The M-tile Means as a Statistics Project and Pedagogical Aid. Issue 3 (15th March 2020) - Savitz, Ryan; Savitz, Fred; DiMarco, David; Hollingsworth, Blane
Abstract: This paper discusses a concept that we call " m -tile means, " which are the arithmetic mean of data values that break a data set into m −1 equal parts. Studying m -tile means can engage students' critical thinking skills and demonstrate the concepts underlying commonly used measures of central tendency, and so they are useful for student projects and accessible statistics discussion.